PENYULUHAN TENTANG DIMENSI MUTU PELAYANAN BPJS DENGA KEPUASAN PASIEN DI KLINIK ARMINA - diandwiana; Fatima Nuraini Sasmita; Rafidaini Sazarni Ratiyun; Vellyza Colin (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Background: Health services have the main objective of improving health and preventing disease with the community as the main target. WHO (World Health Organization) encourages all countries to develop health insurance for all their population (Universal Health Coverage).Purpose: This Community Service aims to increase knowledge about the dimensions of BPJS service quality with patient satisfaction in the work area of ??clinic Armina Regency. . Methods: This activity was carried out by distributing leaflets, conducting counseling and evaluating activities, the implementation of this activity was carried out in the work area of ??the clinicRegency on September 23 to September 25 with a total of 40 patients. Results: In the implementation of the activities that we carried out, there was an increase in patient knowledge after counseling about the dimensions of BPJS service quality with patient satisfaction in the clinic Armina Regency, where the average before counseling was 45 percent, increasing to 80 percent after counseling. In addition, the patient also seemed enthusiastic during the counseling session, this can be seen from the patient's response in the question and answer session Conclusion: From the results of this service activity, there was an increase in patient knowledge about the dimensions of BPJS service quality with patient satisfaction in the work area of clinic Armina.